2012
DOI: 10.7309/jmtm.73
|View full text |Cite
|
Sign up to set email alerts
|

Medical Students’ Use of and Attitudes Towards Medical Applications

Abstract: Background/Aims: With the emergence of new technology (e.g., mobile device applications commonly known as "apps") it is important to establish whether students have access to new technology and their attitudes towards its use prior to its implementation within a medical curriculum. The present study examined medical students' ownership of mobile phones with application support (i.e., smartphones), and their use of and attitudes towards medical applications. Methods: All Monash University medical students in 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
2
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 16 publications
2
24
2
1
Order By: Relevance
“…However, the findings are broadly similar to other studies that have examined the use of smartphones by interns and medical students,4 5 and therefore the authors believe the findings are generalisable to interns in Ireland and other developed countries. Although the response rate may not be as high as would have been desired, it is good considering this was an unsolicited online survey, and higher than other published surveys of smartphone use by interns and medical students 4 5…”
Section: Discussionsupporting
confidence: 87%
“…However, the findings are broadly similar to other studies that have examined the use of smartphones by interns and medical students,4 5 and therefore the authors believe the findings are generalisable to interns in Ireland and other developed countries. Although the response rate may not be as high as would have been desired, it is good considering this was an unsolicited online survey, and higher than other published surveys of smartphone use by interns and medical students 4 5…”
Section: Discussionsupporting
confidence: 87%
“…In this study, we found that the prevalence of medical students who owned a smart device was 87.7%, which was higher than the finding of other similar surveys which showed 79% and 77% in the United Kingdom and Australia, respectively. 12,13 Our study also showed the prevalence of medical students who owned smart devices with installed medical apps on their devices was 87.5%. These findings may suggest that it is a global trend and practice for medical students to own a smart device and use medical apps to support their study and clinical sessions.…”
Section: Discussionmentioning
confidence: 58%
“…Physicians and medical students have high rates of smartphone and tablet computer ownership [13], enabling them to use medical apps. There are over 800,000 apps available for each of the dominant mobile platforms, Apple iOS and Android OS, and a subset of these are categorized by developers as medical apps (2% for Apple iOS [4] and 1% for Android a ).…”
Section: Introductionmentioning
confidence: 99%